Factors affecting consumers in buying drugs through online - Ambar Dwi Erawati; Mona Tiorina Manurung; Chusnul Zulaika3 Zulaika (Enrichment : Journal of Management, 2023)
The behavior of human buying and selling transactions has changed from face-to-face transactions to online transactions. Changes in transaction behavior also occur in the sale and purchase of drugs. People choose to buy online because they think it is cheaper and easier. The community does not consider the safety of the drugs consumed. By using an analytic survey method involving 77 respondents, with a backward stepwise conditional logistic linear regression test analysis, researchers want to examine what factors influence consumers in buying drugs online. The result of this study is that the completeness of the drug, the quality of the drug, the price of the drug, information about the drug, and the ease of obtaining the drug gives a significant value of 0.001 in buying drugs online. There needs to be an evaluation to reduce drug abuse, the public must be careful about the drugs purchased by paying attention to the drug distribution permit, the condition of the drug that is not damaged, and the side effects of drug use. This research can be taken into consideration by business actors in the pharmaceutical sector in increasing drug sales through online by improving these factors.